2005
DOI: 10.1016/j.forsciint.2004.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Allele frequencies for 70 autosomal SNP loci with U.S. Caucasian, African-American, and Hispanic samples

Abstract: 189 samples from 3 different U.S. sample groups Caucasian (74), African American (71) and Hispanic (44) were typed for 70 autosomal genetic markers. These 70 markers are bi-allelic (C/T) short nucleotide polymorphisms (SNPs). For each sample, the 70 SNP markers were typed in 11 unique 6-plexes and a single 4-plex PCR. A total of 10 of the 210 tests (70 loci x 3 populations) for Hardy-Weinberg equilibrium indicated a statistically significant result. In order to evaluate the minimum number of SNP loci needed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 9 publications
(4 reference statements)
0
20
0
Order By: Relevance
“…While automation of SNP detection has improved significantly in recent years enabling millions of SNPs to be examined on hundreds of samples in a relatively short period of time (e.g., 7), due to the large number of loci that must be co-amplified and the inability to easily decipher mixtures, we do not feel that SNPs stand on the horizon as future markers (i.e., replacing STRs) for widespread use in forensic DNA testing. That being said, there are and will likely be important [20]) are shown in (A). Note that only SNP locus 2 in the top panel of (A) has an allele imbalance suggesting that a possible second contributor is present.…”
Section: Discussionmentioning
confidence: 98%
“…While automation of SNP detection has improved significantly in recent years enabling millions of SNPs to be examined on hundreds of samples in a relatively short period of time (e.g., 7), due to the large number of loci that must be co-amplified and the inability to easily decipher mixtures, we do not feel that SNPs stand on the horizon as future markers (i.e., replacing STRs) for widespread use in forensic DNA testing. That being said, there are and will likely be important [20]) are shown in (A). Note that only SNP locus 2 in the top panel of (A) has an allele imbalance suggesting that a possible second contributor is present.…”
Section: Discussionmentioning
confidence: 98%
“…Vallone et al [20] tested 70 SNPs on three populations and found that 12 of them were sufficient to yield a unique genotype for each individual. While our panel of 19 markers did not result in unique genotypes for every individual, we tested over 10 times as many individuals ($2100 versus 189).…”
Section: Discussionmentioning
confidence: 99%
“…Other SNP panels have been proposed [20][21][22]. While the SNPs have usually been selected for high heterozygosity in the target population, they have not generally been tested in multiple populations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, larger SNP panels would be needed for Electronic supplementary material The online version of this article (doi:10.1007/s00414-009-0400-5) contains supplementary material, which is available to authorized users. forensic identification if the same level of discrimination is desired [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%